2021
DOI: 10.1007/978-3-030-86478-1_2
|View full text |Cite
|
Sign up to set email alerts
|

Small Standing-Water Ecosystems in the Transitional Temperate Climate of the Western Balkans

Abstract: Small standing-water ecosystems (SWE, i.e. ponds, lakes, reservoirs), natural or anthropogenic origin, dominate in the global landscape, contributing to the high diversity of habitats and species as well as environmental heterogeneity. Water chemistry, morphometry, climate and the level of human activities are extremely

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…According to theanalyzed data, there is a linkage among rotifer species richness along different altitudinal distributions of lakes, where Lake of Dushku (1380 m) is distinguished by 16 taxa, while Lake of Valamare (2070 m) with four taxa. All taxa identified are new records for their localities [41,42]. In regard to the studies of high mountain lakes in Albania, 31 taxa of rotifers are reported among the zooplankton of analyzed mountain lakes, mostly at the north-eastern range, the elevation of which ranges from 1470 to 2200 m. Among them, the taxa Brachionus quadridentatus, Keratella cochlearis, K. quadrata, Notholca squamula, Euchlanis dilatata, E. incisa, Mytilina ventralis, M. ventralis brevispina, Trichotria tetractis, Colurella uncinata, Lepadella patella, L. patella similis, Lecane flexilis, L. luna, L. lunaris, L. quadrientata, Cephalodella gibba, Trichocerca longiseta, T. rattus, T. similis, T. vernalis, Synchaeta pectinata, Asplanchna priodonta, A. girodi, Testudinella patina, Conochilus unicornis, Hexarthra fennica, and Filinia longiseta were found in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to theanalyzed data, there is a linkage among rotifer species richness along different altitudinal distributions of lakes, where Lake of Dushku (1380 m) is distinguished by 16 taxa, while Lake of Valamare (2070 m) with four taxa. All taxa identified are new records for their localities [41,42]. In regard to the studies of high mountain lakes in Albania, 31 taxa of rotifers are reported among the zooplankton of analyzed mountain lakes, mostly at the north-eastern range, the elevation of which ranges from 1470 to 2200 m. Among them, the taxa Brachionus quadridentatus, Keratella cochlearis, K. quadrata, Notholca squamula, Euchlanis dilatata, E. incisa, Mytilina ventralis, M. ventralis brevispina, Trichotria tetractis, Colurella uncinata, Lepadella patella, L. patella similis, Lecane flexilis, L. luna, L. lunaris, L. quadrientata, Cephalodella gibba, Trichocerca longiseta, T. rattus, T. similis, T. vernalis, Synchaeta pectinata, Asplanchna priodonta, A. girodi, Testudinella patina, Conochilus unicornis, Hexarthra fennica, and Filinia longiseta were found in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The genera that have been recorded as having the highest number of rotifers in Albanian inland waters are Lecane (16 species), Trichocerca (15 species), Brachionus (15 species), Keratella (7 species), Polyarthra (7 species), and Lepadella (6 species). Along with other types of ecosystems, small-standing water ecosystems, including those of glacial origin that are the focus of this work, are thought to be particularly important for biodiversity conservation, and proper management is desperately needed [42]. There are very few publications dedicated to rotifers of glacial lakes [43,44] and the particular features noted by [45] are also the case for the Albanian glacial lakes.…”
Section: Particularities Of Glacial Lakes Distribution and Specific B...mentioning
confidence: 99%
“…The interaction of all these threats has a general negative effect on freshwater habitats [10], and on the specialized vascular flora that colonizes SWEs. Although SWE are globally abundant and their ecological importance is unquestionable, there is a general lack of studies on these habitats, which are often neglected and overlooked by scientific communities and, consequently, in conservation policies [20].…”
Section: Introductionmentioning
confidence: 99%